Influence of readiness measures on planning tourism digital shift - Sorooshian, Shahryar; Azizan, Noor Azlinna; Ismail, Md Yusof (Allied Business Academies, 2021)
Industrial revolution 4.0 is pushing industries toward digitalization including tourism. Although almost all modes of tourism are currently declining as a result of the new COVID-19 pandemic, information and technology is expected to play a role not just during, but also after, the crisis. As a result, the aim of this letter is to formulate a strategic framework for readiness measures for this digitalization transition and see the dependency of the defined measures in tourism industry. Hence, a PROMETEE-based program was used to demonstrate that the top ready clusters for digital tours were not sensitive to the weights of specified readiness measures. This analysis can be used to direct transition planning for top ready tourism clusters